The emotions-music binomial: Conceptualization, taxonomies, scientific evidence and methodological problems - Lorenzo de Reizábal, Margarita (Epistemus. Journal of Studies in Music, Cognition & Culture, 2023)
This study gathers the origin, the historical evolution and the findings and scientific evidence of the most relevant investigations of the last decades on the pairing emotions-music. The main taxonomies of emotions are reviewed, after clarification and conceptualization of the term emotion, qualifying the difference with other terms, such as feeling and state of mind. This work focuses specifically on the analysis of the emotions induced through music and the different theories that historically underlie the attribution of meanings to music. The debate, still open, about whether music does indeed evoke emotions, whether they are perceived or felt, real or attributed is also tackled. Finally, the various methodological problems that limit the validity of the research carried out until now and that have prevented the application of the findings obtained in intervention programs through music in people with emotional dysfunctions are analyzed. Despite being a field of study of great interest, especially for clinical psychology and musical cognition, and despite the great advances in neuroscience, there is still a long way to go.